The solution of the problem of LM-wave diffraction on inclusion in the rectangular waveguide T-junction via Green's theorem - Шульга, С. Н.; Багацкая, О. В.; Ши, Хе (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 1970)
A rigorous method for solving 2D scattering by an arbitrary perfectly conducting inclusion located in the region of a rectangular waveguide T-junction is presented. This method is developed from the approach based on the Green’s theorem. The latter is generalized using special weighting functions satisfying simultaneously the wave equation and the boundary conditions on the scatterer surface. The causes of false resonances arising in the course of solution and elimination methods for them are analyzed. The proposed method is illustrated by results obtained for a thick septum located inside the interaction region. Such approach can be applied for optimization of waveguide junctions.